Methodology and results of creating 3D models of historical and cultural objects using a smartphone equipped with a LiDAR scanner - Kovalchuk, I.; Yukhymyuk, V.; Bogdanets, V. (Land Management, Cadastre and Land Monitoring, 2025)
The article highlights the methodology and results of creating 3D models of historical, cultural and scientific heritage objects of Ukraine using the technology of photographing the studied objects using a smartphone equipped with a LiDAR scanner.As a research object, on the example of which the suitability of a smartphone equipped with a LiDAR scanner for performing surveying work, processing a point cloud of the obtained information about the research object and creating 3D models of the historical, cultural and scientific heritage of Ukraine was tested, the Soil Museum named after Prof. M. M. Godlin, located in the auditorium No. 53 and in the lobby on the third floor of the educational building No. 2 of the NUBiP of Ukraine, was chosen. Its exposition includes more than 200 soil monoliths, selected in various natural zones of Ukraine over the more than 100-year period of the museum’s operation. Given the high scientific and didactic value of this object, it was decided to create its digital 3D model.To implement this task, a schematic diagram (algorithm) was first developed for performing surveying work using a smartphone with a LiDAR scanner and processing the resulting point cloud that reflects the contours of scanned objects. This algorithm is the basis for a substantiated methodology for creating 3D models of objects of historical, cultural and scientific heritage of Ukraine.In the design of mobile devices, LiDAR technology first appeared on rear cameras in 2020 with the release of the iPad Pro and iPhone 12 Pro/iPhone 12 Pro Max. LiDAR is used in them to determine the distances from the camera to the objects under study using laser radiation. Using a smartphone equipped with a LiDAR scanner, the main exhibition of the Soil Museum was photographed using the Polycam program.In the course of further work, based on the point cloud created during the 3D lidar scanning of the Soil Museum, a digital 3D model of the soil monoliths exposition of this object was built (using such software tools as Auto CAD, PIX4D, 3D MAX, Blender).The result of the work performed is a 3D model of the soil monoliths exposition of the Soil Museum, located in auditorium 53 of the second academic building of the NUBiP of Ukraine. At the final stage of the research, the results obtained were verified by comparing the linear dimensions of the stands, determined using a tape measure directly in the Museum, and these same indicators displayed on the 3D model. The error in measuring the linear parameters of the exposition using LiDAR did not exceed 3.10%, i.e. it is acceptable.The created version of the 3D model of the soil monoliths exhibition of the Soil Museum of the National University of Sciences of Ukraine can be used for both educational and popularization purposes. Keywords: LiDAR scanner, Polycam software, smartphone 3D shooting, 3D model, 3D scanning, point cloud.